Reconfigurable graphene-based multi-input multi-output antenna design for THz applications - Reem Hikmat Abd; Hussein A. Abdulnabi (Institute of Advanced Engineering and Science, 2023)
This paper presents a compact graphene-based multi-input multi-output (MIMO) antenna for wireless communications operating in frequency band (0.1-10) THz. This work has been performed with four ports microstrip antennas based on 37×88 μm² a silicon dioxide (Sio₂) substrate and copper on the ground layer, with high isolation by a series of unit cells of graphene selected between adjacent patches to reduce the transmission coefficient and antenna size. Graphene's chemical potential will change by changing the connected DC voltage, leading to bandwidth and resonant frequency variation. The simulation has a reflection coefficient is less than -10 dB at (4.5-10) THz of the frequency scale, mutual coupling (-15 dB), and the gain from (4.7-9) THz is (1.6-6.7254) dB. This paper aims to provide wideband, efficient and reconfigurable with simple graphene-based MIMO antenna for THz applications.